Tradições discursivas: inovações e conservadorismos em atas de câmaras paraibanas dos séculos XIX, XX e XXI - Moura, Adivânia Franca de (2011)
The assumption of this study is that by repetition, discursive traditions establish a link between innovation and conservatism. The study addresses the linguistic and textual features that have changed and that remained in the minutes of the Paraiba borough council meetings that were handwritten, typed and virtualized in the nineteenth, XX and XXI, when the manuscripts were transcribed to the World Wide Web. The study tries to associate the social context of elaboration and utilization of the minutes to the historical context of language, keeping in mind that the texts change with changes in society. It is therefore a diachronic, descriptive and theoretical approach that uses the assumptions of Coseriu (1979, 1987, 1988) and of the German Romanist pragmatists German Romanists Oesterreicher (1996, 2006), Schlieben-Lange (1993), Koch (2008), Kabatek (2006) and Jungbluth (2006) and also looks at Brazilian discursive traditions developed by Simões Kewitz (2009a, 2009b). The corpus of this research is composed of sixty-seven minutes from various boroughs of the state of Paraíba: Zona da Mata, Agreste, Borborema and the Sertão. The originals are kept in private and public historical archives in the boroughs of Paraíba. From these city council minutes, the ones that appear more frequently were selected in the corpus, the structures that constitute them analyzed, with particular emphasis on the XIX, XX and XXI centuries. Based on the assumption that the discursive traditions evoke certain textual and linguistic forms, we used the same proceedings for the analysis of the passive voice as a grammatical element that is repeated in the structure of these minutes. The analysis of the minutes, compared between the centuries cited, showed that their linguistic and textual features changed when transcribed from the record book manuscripts to virtual support. Some information from texts changed their position in the structure of the minutes, other sections have been inserted in the texts and some traditional expressions no longer exist. The analysis also verified some linguistic traits where instances of passive constructions were reduced in the minutes of this century, but it was found that this type of grammatical construction is part of the traditional discursive camera minutes. Given the results, we concluded that, despite the transformations undergone over time, the minutes of the Paraíba camera meetings maintained the structure which identifies it as a discursive tradition.